Late-onset doxorubicin-induced congestive heart failure in an elderly cancer survivor: A case report - Suto, Hirotaka; Suto, Makiko; Inui, Yumiko; Okamura, Atsuo (Frontiers in Cardiovascular Medicine, 2023)
Background Recently, the survival rate of patients with cancer has improved annually due to advancements in cancer diagnosis and treatment technologies. Meanwhile, late-onset complications associated with cancer treatment significantly affect survival and quality of life. However, different from pediatric cancer survivors, there is no unified view on the follow-up of late complications in elderly cancer survivors. We reported a case of congestive heart failure as a late-onset complication of doxorubicin (DXR) in an elderly cancer survivor. Case report The patient is an 80-year-old woman with hypertension and chronic renal failure. She received six cycles of chemotherapy for Hodgkin's lymphoma that started in January 201X-2. The total dose of DXR was 300 mg/m2, and a transthoracic echocardiogram (TTE) performed in October 201X-2, showed good left ventricular wall motion (LVWM). In April 201X, she suddenly developed dyspnea. Upon arrival at the hospital, a physical examination revealed orthopnea, tachycardia, and leg edema. A chest radiograph showed cardiac enlargement and pleural effusion. A TTE showed diffusely reduced LVWM and a left ventricular ejection fraction in the 20% range. After close examination, the patient was diagnosed with congestive heart failure due to late-onset DXR-induced cardiomyopathy. Conclusion Late-onset DXR-induced cardiotoxicity is considered high-risk from 250 mg/m2 or higher. Elderly cancer survivors are at higher risk of cardiotoxicity than non-elderly cancer survivors and may require closer follow-up.